Phonological working memory and linguistic processing speed in inferential reading comprehension - Daniela Balonyi Candal; Clara Regina Brandão de Avila (Psicologia: Reflexão e Crítica)
Abstract Background Phonological working memory has been known as an essential predictor of reading comprehension in children. However, less attention has been paid to processing speed and its interaction with working memory. Main body Research has indicated that higher processing speed of linguistic information contributes to greater availability of memory resources used to comprehend a read text. Objective We tested, using simple mediation models, whether phonological working memory can predict inferential reading comprehension when mediated by linguistic processing speed. Methods To do this, we analyzed information from a database on the assessment of phonological memory (digit span Backward and Forward task), language processing speed (Verbal Fluency and Rapid Automated Naming) and inferential reading comprehension of 66 typical 5th grade students. Results Both phonological working memory and cognitive-linguistic information processing speed were able to predict the inferential reading comprehension of students in the 5th year of elementary school. The mediation analysis showed that rapid automatized naming and working memory (digit span Backward and Forward Task) together, but independently, were able to predict inferential reading comprehension. Conclusion When measured by semantic verbal fluency, linguistic processing speed mediated the prediction of phonological working memory (digits in Forward and Backward order) in inferential reading comprehension.